Character education strengthening model during learning from home: Ki Hajar Dewantara’s scaffolding concept - Hasti Robiasih; Ari Setiawan; Hanandyo Dardjito (Jurnal Penelitian dan Evaluasi Pendidikan, 2021)
In providing educational and learning services to students during the Covid-19 Pandemic, learning is carried out from home. The disparity in learning achievements, especially related to attitude competencies, is strongly experienced during learning from home. This study aims to integrate attitude values through learning with Ki Hajar Dewantara’s scaffolding concept: Identifying, Imitating, Developing, Dissemi-nating. This scaffolding is applied to strengthen the character of junior high school students in Yogyakarta Special Region to become Pancasila students. This is a research and development study that applies a qualitative approach. The respondents of this study were teachers, principals, students, parents, and supervisors of junior high schools in this province. Data were collected using focus group discussion, interview, and observation, then were analyzed using Miles and Huberman models, which comprised data reduction, data display, and inference stages. The results of this study is a character education strengthening model during learning from home applying Ki Hajar Dewantara’s scaffolding concept. This model contributes to the policymaking of character education strengthening during the learning from home online.